2017
DOI: 10.4236/msa.2017.813068
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Effect of Extrusion Velocity on the Spatial Variation of Porosity in a Titanium Dioxide/Binder System

Abstract: Extrusion is a common process technique used to fabricate porous materials such as catalysts and membranes. The performance and efficiency of such materials are governed by porosity and pore distribution. The spatial variation of porosity within the catalyst structure can be linked to process variables in the extrusion processes such as extrusion velocity. A change in extrusion velocity can lead to a change in extrusion pressure. The extrusion pressure effect is a combination of die entry deformation and frict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Ku [28] developed a method using Spurr Low Viscosity Kit epoxy to infiltrate ceramic powders within interparticle pores without causing dispersion or breakage. Alazzawi et al [29] has shown this infiltration method can successfully infiltrate green titanium dioxide extrudates for microstructural characterization with the use of a FESEM and charge mitigation techniques for higher resolution microstructural characterization. This method will be the method investigated for this paper.…”
Section: Micro X-ray Computed Tomography (Micro X-ray Ct)mentioning
confidence: 99%
“…Ku [28] developed a method using Spurr Low Viscosity Kit epoxy to infiltrate ceramic powders within interparticle pores without causing dispersion or breakage. Alazzawi et al [29] has shown this infiltration method can successfully infiltrate green titanium dioxide extrudates for microstructural characterization with the use of a FESEM and charge mitigation techniques for higher resolution microstructural characterization. This method will be the method investigated for this paper.…”
Section: Micro X-ray Computed Tomography (Micro X-ray Ct)mentioning
confidence: 99%